Taylor expansion for matrix functions of vector variable using the Kronecker product - Khang, Nguyen Van; Dat, Dinh Cong; Tuan, Nguyen Thai Minh (Vietnam Journal of Mechanics, 2019)
Taylor expansion is one of the many mathematical tools that is applied in Mechanics and Engineering. In this paper, using the partial derivative of a matrix with respect to a vector and the Kronecker product, the formulae of Taylor series of vector variable for scalar functions, vector functions and matrix functions are built and demonstrated. An example regarding the linearization of the differential equations of an elastic manipulator is presented using Taylor expansion.